My man Godfrey [videorecording (DVD)] - La Cava, Gregory, 1892-1952; Powell, William, 1892-1984; Lombard, Carole, 1908-1942; Brady, Alice, 1892-1939; Patrick, Gail, 1911-1980; Dixon, Jean, 1896-1981; Hatch, Eric, 1901-1973 (Criterion collection, 2001)
A zany millionaire family invites a tramp to be their butler.